The Effect of Training and Competence on Employee Performance with Job Satisfaction as An Intervening Variable In The Department of Communication, Informatics, Statistics, and Code of Semarang City (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research investigates the effect of training and competency on employee performance, with job satisfaction as a mediating variable, at the Department of Communication, Informatics, Statistics, and Encryption of Semarang City. The study uses a quantitative approach with a saturated sampling method, involving all 143 employees as respondents. Results show that both training and competency positively and significantly influence employee performance and job satisfaction. Additionally, job satisfaction plays a mediating role in enhancing performance outcomes. Although various training programs have been implemented, employee participation remains below optimal levels, indicating limited improvement in competencies. These findings emphasize the importance of aligning training and competency development with efforts to improve job satisfaction to achieve better performance. This study contributes to public sector human resource management by offering empirical support for strategies that integrate satisfaction as a critical factor in enhancing workforce productivity.
Keywords: Training, Competency; Employee Performance; Job Satisfaction